Group 1 innate lymphoid cells in Toxoplasma gondii infection. (29th January 2018) - Dunay, I. R.; Diefenbach, A.
Summary: Innate lymphoid cells (ILCs) are a group of lymphocytes that carry out important functions in immunity to infections and in organ homeostasis at epithelial barrier surfaces. ILCs are innate immune cells that provide an early source of cytokines to initiate immune responses against pathogens. Cytotoxic ILCs (i.e. conventional (c)NK cells) and several subsets of helper‐like ILCs are the major branches of the ILC family. Conventional NK cells and group 1 ILCs share several characteristics such as surface receptors and the ability to produce IFN‐γ upon activation, but they differ in their developmental paths and in their dependence on specific transcription factors. Infection of mice with the intracellular parasite Toxoplasma gondii is followed by a strong Th1‐mediated immune response. Previous studies indicate that NK1.1 + cells contribute to the production of IFN‐γ and TNF and cytotoxicity during acute T. gondii infection. Upon oral infection, the parasite infects intestinal enterocytes, and within the lamina propria, innate immune responses lead to initial parasite control although the infection disseminates widely and persists long‐term in immune privileged sites despite adaptive immunity. Upon parasite entry into the small intestine, during the acute stage, ILC1 produce high levels of IFN‐γ and TNF protecting barrier surfaces, thus essentially contributing to early parasite control. We will discuss here the role of innate lymphocytes during T. gondii infection in the context of the only recently appreciated diversity of ILC subsets.